(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2024)
This article explores the impact of using interactive methods in teaching students. It aims to investigate how such methods enhance student engagement, critical thinking, and retention of knowledge. The study was conducted through an experimental design in educational institutions, where traditional and interactive teaching methods were compared. The findings highlight significant improvement in students’ learning outcomes with the implementation of interactive techniques. The article concludes with recommendations for incorporating interactive methods into the curriculum to foster an active learning environment.